Development of a Scale to Measure Perception of Clients in Availing Benefits from Agripreneurs (Indian Journal of Extension Education, 2017)
In the present era, it is being realized that entrepreneurship contributes to development of a country in several ways, viz., assembling and harnessing the various inputs, bearing the risks, innovating and imitating the techniques of production to reduce the cost and increase its quality and quantity, expanding the horizons of the market, coordinating and managing the manufacturing unit at various levels. In fact, the rapid economic development of a country crucially depends upon the number of abilities of entrepreneurs. There was no scale to measure the clients’ perception towards receiving the benefits from agripreneurs. Hence, the present study was designed to develop and standardize a scale for measuring clients’ perception. This was a part of the larger Ph.D. study on “Performance of Agripreneurs under Agri-Clinics and agribusiness centres scheme in Karnataka- An Exploratory study” conducted during 2015-16.